Amyotrophic lateral sclerosis: Analysis of ALS cases in a predominantly admixed population of Ecuador. Issue 1 (March 2014) - Bucheli, Miriam; Andino, Andres; Montalvo, Mayra; Cruz, Jose; Atassi, Nazem; Berry, James; Salameh, Johnny
Abstract Recent studies suggest amyotrophic lateral sclerosis (ALS) prevalence, incidence, and age of onset are heterogeneous across populations. These include studies from South America (SA) where lower prevalence, earlier onset, and reduced survival time of ALS are reported. However, the scarcity of epidemiological and clinical data confounds effective comparison. To investigate ALS incidence in the predominantly admixed population of Ecuador, we analyzed patient data. We analyzed case data from two major hospitals. To confirm diagnosis, we evaluated clinical and EMG examinations in a cohort of patients. For 2000–2012, we found 116 patients with ALS diagnosis in the two hospitals. Crude incidence was 0.2–0.6 per 100, 000. Median age of onset was 54.3 (+ 15.06 SD). Clinical re-evaluation found misdiagnosis in three cases in the cohort. In conclusion, ALS incidence in the Ecuadorian hospital population is in accord with rates reported in recent studies for other admixed populations, and lower than that in the United States and Europe. Our study found that appropriate EMG administration and interpretation for the purposes of supporting a diagnosis of ALS with current consensus guidelines prevent adequate use of this test as an essential tool in the evaluation and diagnosis of ALS. Training for required standardization in Ecuador is recommended.